2019
DOI: 10.3343/alm.2019.39.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot Multiplexed Steroid Profiling Using Liquid Chromatography Tandem Mass Spectrometry in Korean Neonates

Abstract: Background Screening for congenital adrenal hyperplasia (CAH) using immunoassays for 17α-hydroxyprogesterone generates many false-positive results. We developed and validated a liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay for simultaneous quantification of nine steroid hormones in dried blood spot (DBS) samples, and established reference intervals for these hormones. Methods We examined our method for linearity, precision, accuracy, extraction recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…There have been various studies investigating the feasibility of increasing the number of analytes in the steroid panel to increase specificity and sensitivity [ 44 , 45 , 46 , 47 , 48 ]. There are studies that show that the inclusion of 21-deoxycortisol and 11-deoxycortisol is more specific for detecting SWCAH by excluding β-hydroxylase deficiency [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been various studies investigating the feasibility of increasing the number of analytes in the steroid panel to increase specificity and sensitivity [ 44 , 45 , 46 , 47 , 48 ]. There are studies that show that the inclusion of 21-deoxycortisol and 11-deoxycortisol is more specific for detecting SWCAH by excluding β-hydroxylase deficiency [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the diagnosis, prognosis, and management of such diseases strongly depend on accurate quantification of steroid hormones in biological fluids. Imbalances in production or metabolism of steroids lead to a wide range of steroid related disorders, sometimes complex adrenal diseases, including congenital adrenal hyperplasia (CAH) [71][72][73][74]82,83], adrenal cancer [4,6,7,45,75,76], hyperaldosteronism [45,[84][85][86][87], Cushing's syndrome [68], disorder of sexual development (DSD) [44], and polycystic ovary syndrome (PCOS) [44,69,88]. For some of these disorders, it is still open to debate on which steroids are most appropriate to be quantified for the related diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these results were interpreted as appropriate for the child’s gestational age. Defining normal cortisol values is difficult in the neonatal period as studies have shown a large range of reference values [ 10 ]. There was no evidence of hypoglycemia, hyponatremia, hyperkalemia, lethargy, or vomiting.…”
Section: Clinical Casementioning
confidence: 99%